The effect of root canal sealers and timing of cementation on the microlekage of the parapost luted with resin cement - Ahmed M. Al Kahtani (Saudi Dental Journal)
Objectives: The objectives of the study were to study the effect of root canal sealers either eugenol or non-eugenol and timing of cementation on microleakage of the parapost luted with resin cement. Materials and methods: Seventy extracted human, single-rooted teeth were instrumented using a crown-down technique. All teeth were instrumented up to a size 50 .04 taper ProFile followed by the use of Gates Glidden drills from size 2 up to 5. Following instrumentation, the teeth were randomly divided into four experimental groups of fifteen teeth each, based on type of root canal sealer (eugenol or non-eugenol sealer) and timing of post cementation (immediate or delayed). The remaining ten teeth were divided into two control groups with five teeth per group. All teeth were tested for microleakage using a fluid filtration method. Results: The microleakage of the paraposts luted with resin cement increased over time, irrespective of sealer type or timing of post cementation. Immediate post cementation following obturation with AH26 (non-eugenol sealer) produced the least microleakage at all three time periods at 24 h, 2 months and 3 months. Conclusions: The microleakage paraposts luted with resin cement was not influenced by either sealer type or timing of post placement. All experimental groups demonstrated a significant increase in microleakage over time as well as the presence of voids at the resin–dentin interface. Keywords: Root canal sealer, Parapost, Microleakage, Resin cement